2016
DOI: 10.1165/rcmb.2016-0096oc
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species/Hypoxia-Inducible Factor-1α/Platelet-Derived Growth Factor-BB Autocrine Loop Contributes to Cocaine-Mediated Alveolar Epithelial Barrier Damage

Abstract: Abuse of psychostimulants, such as cocaine, has been shown to be closely associated with complications of the lung, such as pulmonary hypertension, edema, increased inflammation, and infection. However, the mechanism by which cocaine mediates impairment of alveolar epithelial barrier integrity that underlies various pulmonary complications has not been well determined. Herein, we investigate the role of cocaine in disrupting the alveolar epithelial barrier function and the associated signaling cascade. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…An earlier study showed that HIF-1a and PDGF cooperate with Akt signaling to mediate autocrine regulation which promotes angiogenesis in endothelial cells [39]. Another study reported an intriguing mechanism of an autocrine loop involving reactive oxygen species (ROS)/HIF-1a/PDGF in lung alveolar epithelial cells [40]. Taken together, our findings underpin the proangiogenic and cardioprotective role of exosome-delivered HIF-1a in infarcted heart via VEGF and PDGF.…”
Section: Discussionsupporting
confidence: 61%
“…An earlier study showed that HIF-1a and PDGF cooperate with Akt signaling to mediate autocrine regulation which promotes angiogenesis in endothelial cells [39]. Another study reported an intriguing mechanism of an autocrine loop involving reactive oxygen species (ROS)/HIF-1a/PDGF in lung alveolar epithelial cells [40]. Taken together, our findings underpin the proangiogenic and cardioprotective role of exosome-delivered HIF-1a in infarcted heart via VEGF and PDGF.…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, hypoxia also increased endothelial monolayer permeability allowing vasoactive factors to reach PASMC (Partridge, ; Yang et al . ). Thus, O 2 sensing mechanisms in multiple vascular cell types contribute to the activation of diverse responses that collectively define the responses to acute and chronic hypoxia (Gao et al .…”
Section: Acute Hpv and Chronic Hypoxia‐induced Vascular Remodellingmentioning
confidence: 97%
“…Long‐term abuse of MA can cause pulmonary toxicity with clinical manifestations: pulmonary oedema, inflammation and pulmonary hypertension . A growing body of evidence indicates that alveolar epithelial cells play an important role in the protecting against the toxic stimulants to maintain pulmonary homeostasis . Therefore, disruption of alveolar epithelium may be the key contribution to chronic pulmonary toxicity induced by MA.…”
Section: Introductionmentioning
confidence: 99%